Dyslexia: communication problems in interaction - Subramaniam, Vijayaletchumy; Kunasegran, Kavenia (Science and Engineering Research Support Society, 2020)
The purpose of this study was to explore the significant communication problems of children with dyslexia. An effective communication requires the capability of the individual to demonstrate the three following domains, a) cognitive, b) behavioural and c) emotional. Thirty-four children were recruited from Malaysia Dyslexia Association for this study. Three modes of data collection were carried out, namely through observations, surveys and interviews. In this study, the researcher applied triangulation data by collecting three forms of data sources, namely questionnaires, audio and video recording and research field notes to increase validity and reliability of the research. Findings of the study has found that the dyslexic children exhibit social skills problems in the communication aspect. In relativity of language acquisition, learning and speech, the cerebellar theory emerges as a complex theory on how the cognitive, behavioural and biological domain coexists together. Results from the findings demonstrated that the dyslexic children show difficulties in these 4 areas, a) affective understanding, b) initiating interactions, c) responding to interactions, and d) maintaining interactions.